1992
DOI: 10.1044/jshr.3505.1105
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing Perceptions of the Communicative Competence of an Adult Augmentative and Alternative Communication System User

Abstract: The effects of aided message length, partner reauditorization, and observer background on perceptions of the communicative competence of an adult augmentative and alternative communication (AAC) system user were examined. Two groups of subjects participated: naive adults with minimal exposure to nonspeaking persons, and speech-language pathologists currently working with AAC users. Four scripted videotaped conversational conditions involving an AAC user and a normally speaking partner were employed to manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
2
31
1
Order By: Relevance
“…Yuker (1994) indicated that competence is a factor that affects attitudes when the area of competence is important to the observer. The studies reviewed here include initial attempts to investigate the effects of communicative competence on listener attitudes; however previous work suggests that competency of individuals using AAC involves more factors than response latency and prompting and may be differentially valued according to the observer (Bedrosian, Hoag, Calculator, & Molineux, 1992;Bedrosian, Hoag, Johnson, & Calculator, 1998;Light, 1989;Schlosser, 2003a). Triandis et al (1984) stated ''when people have no established habits about a certain behavior they do what is socially desirable, consistent with their self-concepts, intrinsically enjoyable, and has good perceived consequences'' (p. 28).…”
Section: Changing Behaviorsmentioning
confidence: 99%
“…Yuker (1994) indicated that competence is a factor that affects attitudes when the area of competence is important to the observer. The studies reviewed here include initial attempts to investigate the effects of communicative competence on listener attitudes; however previous work suggests that competency of individuals using AAC involves more factors than response latency and prompting and may be differentially valued according to the observer (Bedrosian, Hoag, Calculator, & Molineux, 1992;Bedrosian, Hoag, Johnson, & Calculator, 1998;Light, 1989;Schlosser, 2003a). Triandis et al (1984) stated ''when people have no established habits about a certain behavior they do what is socially desirable, consistent with their self-concepts, intrinsically enjoyable, and has good perceived consequences'' (p. 28).…”
Section: Changing Behaviorsmentioning
confidence: 99%
“…The statements were derived from previously used communicative competence scales (Bedrosian, Hoag, Calculator, & Molineux, 1992;Todman, 2000) that had good internal consistencies and had been found to be sensitive to the effects of experimental manipulations. The criteria for selection of statements were scale brevity combined with coverage of Light's (1989) four interrelated areas of communicative competence: linguistic, operational, social, and strategic.…”
Section: Communicative Competence Scalementioning
confidence: 99%
“…Along the same lines, communicative competence in AAC practice should be assessed in relation to the communication repertoires demonstrated by two communication participants (e.g., a person who uses AAC and a natural speaker) in their dyadic communication. Like perceptions of the communicative competence of a naturally speaking dyad, Bedrosian et al [69] and Smith and Cascella [55] recommended that all three types of observers (a person who uses AAC, a communication partner, and a third-party observer) perceive the communicative competence in AAC practice. However, the communicative competence of people who use AAC has been mainly perceived by communication partners and third-party observers during the past decades.…”
Section: The Evolution Of Communication Competence In Aac Practicementioning
confidence: 99%
“…Although the validity of reports from people who use AAC is questionable [74], having them rate communicative competence is still a good option, because individual ratings for communicative competence do not need to be compared with others, as only the participants can determine whether a mutual communication goal has been reached. All three methods are recommended for perceiving communicative competence in AAC practice [54,55,66,69,72]. Interviews and observations can be used to complete the perception process.…”
Section: The Evolution Of Communication Competence In Aac Practicementioning
confidence: 99%